2009
DOI: 10.3109/10641960902927978
|View full text |Cite
|
Sign up to set email alerts
|

Role of Heme Oxygenase in Modulating Endothelial Function in Mesenteric Small Resistance Arteries of Spontaneously Hypertensive Rats

Abstract: It has been proposed that endothelial dysfunction is due to the excessive degradation of nitric oxide (NO weeks. Systolic blood pressure (SBP) was measured (tail cuff method) before and after treatment. Mesenteric small resistance arteries were mounted on a micromyograph. Endothelial function was evaluated as a cumulative concentration-response curve to acetylcholine (ACH), before and after preincubation with N(G)-methyl-L-arginine (L-NMMA, inhibitor of NO synthase), and to bradykinin (BK). In SHR treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
3
3
0
Order By: Relevance
“…In a basic experiment, the SHR model exhibited an obvious decrease in HO-1 expression levels compared with WKY [18], indicative of HO-1 system dysfunction in hypertension. Upregulating the activity and expression of HO-1 could inhibit the process of hypertension [17,19], which coincides with our results. The associated mechanisms involve restoration of endothelial function [17], inhibition of VSMC proliferation [20], suppression of kidney oxidative and inflammatory injury [21], amelioration of vascular regulative factors [22,23] and direct relaxation of blood vessels by CO [23].…”
Section: Resultssupporting
confidence: 91%
“…In a basic experiment, the SHR model exhibited an obvious decrease in HO-1 expression levels compared with WKY [18], indicative of HO-1 system dysfunction in hypertension. Upregulating the activity and expression of HO-1 could inhibit the process of hypertension [17,19], which coincides with our results. The associated mechanisms involve restoration of endothelial function [17], inhibition of VSMC proliferation [20], suppression of kidney oxidative and inflammatory injury [21], amelioration of vascular regulative factors [22,23] and direct relaxation of blood vessels by CO [23].…”
Section: Resultssupporting
confidence: 91%
“…For instance, the inoculation of PGPRs improved salinity stress tolerance in wheat through alleviating the activity of numerous antioxidant enzymes such as manganese-dependent superoxide dismutase (MnSOD), POD, CAT, GR, and APX (Bharti et al, 2013 ). The findings are in line with this study, where the excess Co significantly increased enzyme activity responsible for dismutation of O 2 , which were further increased by inoculation with archaea (Porteri et al, 2009 ). Furthermore, our results revealed that the activities of Grx, Trx, and peroxiredoxins, families of thiol oxidoreductases, were also increased, but again, they were higher in archaea combined with Co treatment.…”
Section: Discussionsupporting
confidence: 91%
“…In the aortas and MRA of adult SHR, Ach-induced endothelium-dependent vasorelaxation was significantly milder versus in WKY rats. This indicates a partial impairment associated with the endothelium-dependent NO system in genetic hypertension, as previously suggested by other authors [23,24,25,26]. As expected, Ach failed to relax the aortas of LNHR, suggesting that chronic inhibition of NO synthesis results in the complete impairment of endothelium-dependent NO release, which is mainly responsible for Ach induced-vasodilatation in conductance vessels [27,28,29].…”
Section: Discussionsupporting
confidence: 61%